2021
DOI: 10.1590/1807-1929/agriambi.v25n7p446-452
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic efficiency and production of Annona squamosa L. under salt stress and fertilization with NPK

Abstract: HIGHLIGHTS Electrical conductivity of water of 3.0 dS m-1 reduces the chlorophyll synthesis and production of custard-apple. NPK recommendation of 100-125-125, 125-125-100 and 125-125-125% cause more damage to the cell membrane. Reduction in the quantum efficiency of custard-apple under salt stress is indicative of photoinhi-bitory damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Similar results were observed by Ferreira et al (2021) in a study conducted with custard apple (Annona squamosa L.) under salt stress (0.8 and 3.0 dS m -1 ), in which they found reduction of 18.98% in the Fv of plants irrigated with the highest ECw (3.0 dS m -1 ), at 695 DAT.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar results were observed by Ferreira et al (2021) in a study conducted with custard apple (Annona squamosa L.) under salt stress (0.8 and 3.0 dS m -1 ), in which they found reduction of 18.98% in the Fv of plants irrigated with the highest ECw (3.0 dS m -1 ), at 695 DAT.…”
Section: Resultssupporting
confidence: 87%
“…Plants irrigated with water of the highest salinity (4.0 dS m -1 ) had an increase of 7.13% (45.9) compared to those cultivated with ECw of 0.8 dS m -1 . The increase in Fo is indicative of damage to the photosynthetic apparatus caused by salt stress, since this variable indicates the loss of light energy, a situation that occurs in a state of oxidation of the quinone (primary electron receptor) in the reaction center (P680), hindering the transfer of energy from photosystem II (Dias et al, 2021). Sá et al (2021), evaluating the photosynthetic efficiency of sugar apple (Annona squamosa L.) under salt stress (ECw varying between 0.8 and 3.0 dS m -1 ), found an increase (7%) in Unlike the effect observed on Fo (Figure 3A), the maximum fluorescence was reduced with the increasing salinity of irrigation water (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…et al, 2019. These results indicate a greater loss of energy by the chlorophyll complex, which may be related to the greater difficulty of plants in absorbing water and optimizing the process of free energy consumption (F. N. Ferreira et al, 2021). In line with this study, Andrade et al (2019) evaluated the tolerance of cowpea (Vigna unguiculata L.…”
Section: Resultsmentioning
confidence: 64%
“…48 Using water with different electrical conductivities and adding nitrogen, phosphorus and potassium salts can alleviate salt stress in plants by promoting ion homeostasis. 49,50 It has been reported that a mixture of organic matter, sulfur, and gypsum can reduce soil salinity and maintain soluble and exchangeable cations, promoting plant growth. 51 Iron (Fe) availability in saline soils is reduced, resulting in Fe-deficient crops.…”
Section: Salinity Stressmentioning
confidence: 99%